Alternative Method for Calculating Runoff Coefficient Based on Discharge Simulation Model by Applying Unit Hydrograph Concept (Kali Kripik Sub Watershed Case Study) - BUDI KARTIWA; GATOT IRIANTO (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2001)
Comparison of two method on calculating runoff coefficient (Cr), is discussed in this paper i.e. classical method and alternative method. The first one calculates Cr based on the hydrograph separation analyses, and the second one based on the discharge model simulation by applying unit hydrograph concept. The classical Cr values is calculated using simple method and the alternative Cr values is calculated using H2U (Hydrogramme Unitaire Universel) transfer rainfall-discharge model, for 47 rainfall and discharge events from September 1998 to March 1999 on Kripik sub Watershed. The H2U model calculates discharge based on convolution product between excess rainfall and hydrological network density that was represented by probability density function. The Cr value according to this model is determined when the Cr is resulting the best discharge simulation. During the period of September 1998 to March 1999, the classical Cr value varied between 2,8 to 69,1%, while alternative Cr between 1,0 to 48,8%. The smallest and the biggest differences between classical and alternative Cr values were 0,3% and 26,5%, respectively. According to regression analyses and Nash-Sutcliffe criterion, the coefficient of determination (R2) and the coefficient of efficiency (F) were 0,9312 and 0,6829, respectively. Statistically, these values indicate that the alternative Cr value was similar to classical one.